Design-Based Research in der Deutschdidaktik. Sprach-, literatur- und mediendidaktische Forschungsprojekte : Design-Based Research in German Didactics. Research Projects on Language, Literature and Media Didactics - Topalovi´c, Elvira; Drepper, Laura (EDeR. Educational Design Research, 2024)
Das Editorial führt in das Special Issue Design-Based Research in der Deutschdidaktik. Sprach-, literatur- und mediendidaktische Forschungsprojekte ein, das aus insgesamt drei Academic Articles und drei Practice Illustrations besteht. Sie geben einen Einblick in aktuelle sprach-, literatur- und mediendidaktische D(B)R-Projekte. The editorial introduces the special issue Design-Based Research in German Didactics. Research Projects on Language, Literature and Media Didactics, which consists of a total of three Academic Articles and three Practice Illustrations. They provide an insight into current D(B)R projects in language, literature and media didactics.